Nodes and Boundaries of Global Communications: Notes on the Translation and Dubbing of Audiovisuals - Paolinelli, Mario (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe quality of dubbing is threatened by the recent developments of the audio-visual market. This holds true in Italy and surely elsewhere. The actors of the film industry (studios, directors, dialogue-writers, directors of dubbing) must fight for the right to have “good” dubbing. Some proposals are given. The absence of rules is seriously damaging the moral rights of the original film-makers, the professionalism of the technical and artistic sector, the target language and above all viewers, including the children.